A Brief Comment on Vasa Vasorum of Human Saphenous Vein: relevance for Coronary Artery Bypass Surgery - Loesch,Andrzej (2021)
Abstract The importance of the vasa vasorum and blood supply to the wall of human saphenous vein (hSV) used for coronary artery bypass grafting (CABG) is briefly discussed. This is in the context of the possible physical link of the vasa vasorum connecting with the lumen of hSV and the anti-ischaemic impact of this microvessel network in the hSV used for CABG.